ANTIBIOTIC SUSCEPTIBILITY TEST OF MUCOID ESCHERICHIA COLI ISOLATES CAUSING DIARRHEA IN BALI CATTLE - Everetta, Daniella; Suarjana, I Gusti Ketut; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2025)
Escherichia coli mucoid is a common bacterium that frequently causes digestive diseases in both humans and animals, particularly bali cattle. This study aimed to determine the antibiotic sensitivity pattern of E. coli. The testing was conducted using the Kirby-Bauer method with the disc diffusion technique to evaluate the susceptibility of E. coli to four antibiotics: Streptomycin, Doxycycline, Trimethoprim-Sulfamethoxazole, and Bacitracin. The results showed that the mucoid E. coli was sensitive to doxycycline, showed intermediate sensitivity to streptomycin and trimethoprim-sulfamethoxazole, and was resistant to bacitracin. The appropriate treatment for diarrhea in Bali cattle caused by mucoid E. coli is doxycycline, as the study indicated that the mucoid E. coli isolates were sensitive to this antibiotic. The use of antibiotics with intermediate sensitivity or those that are resistant is not recommended.